Lexical semantic features of banking and finance terms ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
Globalization and integration of financial and economic procosses taking place in the world economy have stimulated the country’s economic and financial sectors to a qualitatively new level. Comparative analysis of the financial and economic terminology of the banking-finance terms in the world linguistics on the examples of English and Uzbek languages not only develop systemic relationship in the lexicon of the studied language, but also interdisciplinary comparative-typological studies, banking-finance terminology and dictionary of banking-finance terms to identify and analyze the important and distinctive features that are important for creating and the differences in lexical-semantic phenomena.